PENGARUH KEJELASAN SASARAN ANGGARAN DAN AUDIT KINERJA TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Studi Empiris Kabupaten Mamuju Tengah) - Ari Sarwo Indah Safitri (Bongaya Journal for Research in Accounting (BJRA), 2019)
This research was conducted with the aim of: (1) Knowing and analyzing the influence of theclarity of the budget target on government performance accountability; (2) Knowing and analyzing the effect ofaudit performance on government performance accountability; (3) Knowing and analyzing the influence ofclarity of budget targets and performance audits simultaneously on the performance accountability ofgovernment agencies; (4) Knowing and analyzing organizational commitment can moderate the relationshipbetween clarity of budget goals and performance audits with performance accountability of governmentagencies This study uses primary data through a survey of all Regional Work Unit (SKPD) in Mamuju TengahDistrict, which amounts to 33. This research was conducted for three months, from December to February 2019.Data were analyzed using the Partial Least Square (PLS) approach. The results of this study indicate that: (1)Clarity of budget targets has a positive and significant effect on the performance accountability of governmentagencies; (2) performance audits have a positive and significant effect on the performance accountability ofgovernment agencies; (3) clarity of objectives has a positive and significant effect on the accountability ofperformance of government agencies by being moderated by organizational commitment; (4) performance auditshave a positive and significant effect on the performance accountability of government agencies by beingmoderated by organizational commitment.